Racism in Bom-Crioulo: The doublethinking as a tool of the society of control - Sales , Maria da Luz Lima; Sousa , Carlos Wilker Silva de (Seven Editora, 2023)
The present work aims to analyze the relations of veiled racism between the characters of the narrative Bom-Crioulo, by Adolfo Caminha (1998), from the concept of "doublethink" presented by George Orwell (2013), in his work Nineteen Eighty-Four. To better understand the conditioning factors of this current thought, we seek to analyze the master-slave relationship of the protagonist Amaro, in the light of the concept of disciplinary society and control, according to Gilles Deleuze (1992), from the historical context of the literary work. The present research goes through the novel of the Brazilian author in order to answer the following question: is racism, in the Caminhian work, perpetuated by the characters through a double thought? To broaden the understanding of racism in society, examples of this practice were used both in the sociocultural context in which the work takes place and in Brazilian society of the twenty-first century. The results indicate a constant displacement of the realist-naturalist novel in question, between an institutionalized control and a kind of flexible control over the color of the skin of the Caminhian hero and his condition as a low-ranking sailor. DOI:https://doi.org/10.56238/alookdevelopv1-078